An Integrated Ecological Approach to Mapping Variations in Collectivism Within China: Introducing the Triple-Line Framework. (February 2021) - Ren, Xiaopeng; Cang, Xiaohui; Ryder, Andrew G.
Measurable regional variations in collectivism have been found across the Chinese mainland, challenging the simple classification of China as a "collectivistic society" in cross-national studies. In previous studies, a small number of distal or proximal ecological factors have been used to explain these regional variations of collectivism. However, there has been little consensus on which ecological factors best predict regional collectivism. In this article, the authors propose the "triple-line framework, " an integrated perspective on regional variations in collectivism. This framework divides China into four regions using three lines—the Hu Huanyong Line, the Great Wall Line, and the Qinling–Huaihe Line—according to their ecological, historical, and social characteristics. A growing body of empirical research is largely consistent with this framework. The authors conclude by discussing the potential for this framework to generate new, testable hypotheses and consider some ways in which this approach to intranational variation could be used by cultural psychologists working in other parts of the world.